Fostering application of more exact methodological and statistical procedures in sport management research - Naumovski, Goce; Stojkov, Aleksandar; Naumovski, Aleksandar; Naumovski, Vasko (Journal of Physical Education and Sport, 2013)
This study critically examines the basic methodological and statistical characteristics of selected up-to-date sport management researches. They are reviewed in relation to the applied research types, determination, verification and comparison of metrical characteristics of measurement instruments (questionnaires and judgment scales), as well as to the applied multivariate methods in manifest and latent space. In particular, the factor analysis, taxonomic analysis, regression analysis (classical, stepwise, hierarchical), canonical correlation analysis, analysis of covariance and multivariate analysis of variance are reviewed. On the grounds of characteristics of these researches, the endeavours for complex application of methodological statistical procedures are outlined as inevitable for the forthcoming sport management research. The application of multivariate statistical procedures in latent space within the longitudinal and experimental research is particularly accentuated. Lastly, the need for fostering the application of multivariate methodological and statistical procedures in the framework of replicated research of previously factorized results is underscored. [PUBLICATION ABSTRACT]